THE EFFECT OF GROUP INVESTIGATION–TYPE COOPERATIVE LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES AT GRADE V SD NEGERI 101859 RAMBAI ACADEMIC YEAR 2019/2020 - Feronika Tarigan; Rumiris Lumbangaol; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research utilized a descriptive method which was conducted in one class, namely the experimental class. The instrument used to collect data was multiple choice questions. The hypotheses were examined by the